What Motivates Tourists to Share Information on Social Media - Mandasari, Virginia; Majid, Nurkholish (Fakultas Ekonomi Universitas Samudra, 2023)
This research aims to examine the phenomenon of information sharing that occurs in groups in social media by uisng formal and informal communication that affect Transactive Memory System (TMS). This research also examines how TMS’s role on sharing information in groups as well as in self-relevant values. This research imply that formal and informal communications positively affect TMS, so it has a positive effect on self-relevant value. Therefore, transactive memory systems became a good mediator between formal and informal communication with self-relevant value. By sharing information in the group, their image will increase in front of people outside the group (self-image congruity). The group is created for the purpose to re-share the information with the other group who successfully invite potential tourists will increase self-relevant value in other groups.